Nivel de información de los estudiantes de comunicación social, en el aprovechamiento de las becas que ofrece la Universidad Nacional De Loja, a través del departamento de Bienestar Universitario - Sotomayor Torres, Luis Augusto (2015)
The National University of Loja like most institutions of higher education, provides scholarships to students to explore careers that are offered, which is why the Alma Mater lojana through the Department of University Welfare, provides this service to Students who meet certain requirements, according to the type of scholarship you're applying to. However, the disinformation of the university community, and in this case in point, students of Social Communication, is the main reason why students do not take advantage of this service. The present research had as main objective, the report efficiently and effectively about scholarships to students of Social Communication of the National University of Loja. To find out what level of information on the subject in question are students, direct students and teachers of the race in Social Communication Sciences, National University of Loja surveys are mainly used. In developing this work, the students showed little knowledge about scholarships at the University, with the prevalence of misinformation, more than 70% in the surveyed students. Also not a current outreach program was found by University Well, in this issue of vital importance not only for Social Communication, but to the entire university community. Therefore it concluded that there is misinformation about the scholarship students of Social Communication. Finally, a proposal was made comprising: talks to students, teachers, provision of information leaflets to students of Social Communication, dissemination through social networks and implementation of a hyperlink on the website of the UNL, on scholarships; thus the research aims to inform about the subject matter of this work, the aforementioned actors. Keywords: Scholarships, Knowledge, Disinformation, Students, University.